Preservation of Lingzhi (Ganoderma Lucidum) White Fresh Fruit - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Lingzhi (Ganoderma lucidum) has highly valued nutritional properties. Its potential beneficial effects on human health may be termed functional foods. The production of fresh Ganoderma lucidum is increasing. This trend is expected to continue in the coming years. Fruit boby of Ganoderma lucidum has a short shelf-life owing to its high rate of respiration and perishibility. In order to extend the fresh appearance or shelf-life of Ganoderma lucidum white fresh fruit bodies, we investigated on the preservation of Ganoderma lucidum fresh fruit body. Our results showed that washing Ganoderma lucidum white fresh fruit bodies with 0.15% peroxyacetic acid in 30 seconds and keeping them in PA bag without hole in 4 o C could maintain their weight and eliminate coliforms effectively.Keywords: Ganoderma lucidum, Lingzhi, shelf-life, Peroxyacetic acid, Coliforms, Preservation